Jews in twentieth century Ireland : refugees, anti-semitism and the Holocaust - Keogh, Dermot 1945- (Cork Univ. Press, 1998)
This book analyzes the relationship between the Irish State and the Jewish community in the 1930s. The author assesses Ireland's humanitarian record during the Holocaust and finally traces the history of the Irish Jewish community from the 1950s to the 1990s.